ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PT EXPRESS TRANSINDO UTAMA (TAXI), TBK - Anugrahwati Ariatma (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2020)
This study aims to determine and analyze bankruptcy predictions at PT Express Transindo Utama (TAXI) Tbk using the Altman Z-score model, whether PT Express Transindo Utama (TAXI) Tbk is experiencing symptoms of financial problems and is in the bankrupt category or is included in the non-bankrupt category based on interpretation of the Altman Z-score model. The type of data used in this research is quantitative and the data source used is secondary data. The analytical tool in this study using the Altman Z-score model. From the results of the analysis based on calculations that have been carried out on the financial statements of PT Express Transindo Utama (TAXI) Tbk in 2015 and 2016 the company is included in the gray area category because the Z-score shows a value of 1.1 <Z <2.6. But in 2017 and 2018 the Z-score shows a Z value <1.1, so the company is in the bankrupt category or the company is experiencing serious financial problems. This is due to the larger current debt of the company compared to the current assets of the company as well as the less than maximum revenue earned and the large operating costs of the company. Companies can overcome this by reducing debt and increasing revenue.